2021
DOI: 10.1101/2021.04.10.439288
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

ADAM17 inhibition prevents neutrophilia and lung injury in a mouse model of Covid-19

Abstract: Severe coronavirus disease 2019 (Covid-19) is characterized by lung injury, cytokine storm and increased neutrophil-to-lymphocyte ratio (NLR). Current therapies focus on reducing viral replication and inflammatory responses, but no specific treatment exists to prevent the development of severe Covid-19 in infected individuals. Angiotensin-converting enzyme-2 ACE-2) is the receptor for SARS-CoV-2, the virus causing Covid-19, but it is also critical for maintaining the correct functionality of lung epithelium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 45 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…A last natural strategy in the context of scenario 2 to reduce ACE2 overactivity, responsible for the exacerbated inflammatory responses in COVID-19, is to target ACE2 shedding via the inhibition of ADAM17 [120]. Two ADAM17 inhibitors have been tested in animal models of COVID-19, apratastat (TMI-005) and TMI-1, resulting in a significant reduction in the production of pro-inflammatory cytokines as well as in protective effects against lung injury associated with COVID-19 [122] .…”
Section: Ras-targeting Drugs In Covid-19mentioning
confidence: 99%
“…A last natural strategy in the context of scenario 2 to reduce ACE2 overactivity, responsible for the exacerbated inflammatory responses in COVID-19, is to target ACE2 shedding via the inhibition of ADAM17 [120]. Two ADAM17 inhibitors have been tested in animal models of COVID-19, apratastat (TMI-005) and TMI-1, resulting in a significant reduction in the production of pro-inflammatory cytokines as well as in protective effects against lung injury associated with COVID-19 [122] .…”
Section: Ras-targeting Drugs In Covid-19mentioning
confidence: 99%
“…Therefore, inhibiting ADAM-17 activity seems to be a rational option in severe cases of COVID-19. Experimental evidence has been shown that the inhibition of ADAM-17 protects against lung inflammation by reducing cytokine storm and excessive neutrophil recruitment to the lung in a mouse model associated with COVID-19 [92]. However, ADAM-17 has a broad regulatory role in human biological processes.…”
Section: Novel Treatment Options Targeting Defective Efferocytosis In Covid-19mentioning
confidence: 99%